Succession of the multi-site microbiome along pancreatic ductal adenocarcinoma tumorigenesis - Zhu, Yiqing; Liang, Xiao; Zhi, Mengfan; Li, Lixiang; Zhang, Guoming; Chen, Changxu; Wang, Limei; Wang, Peng; Zhong, Ning; Feng, Qiang; Li, Zhen (Frontiers in Immunology, 2024)
Background To investigate microbial characteristics across multibody sites from chronic pancreatitis (CP), through pancreatic benign tumors, to pancreatic ductal adenocarcinoma (PDAC) at different stages. Methods 16S ribosomal RNA (rRNA) amplicon sequencing was conducted on saliva, duodenal fluid, and pancreatic tissue obtained via endoscopic ultrasound-guided fine needle aspiration (EUS-FNA) of patients with CP, pancreatic benign tumors, PDAC in stage Ⅰ/Ⅱ, Ⅲ, and Ⅳ. The neutral community model (NCM) assessed the microbial assembly contribution and MaAslin2 identified the differential microbes. Results From CP to stage IV PDAC patients, there was a marked surge in influence of salivary and duodenal microbiota on constitution of pancreatic microbial communities. Our observations revealed a successive alteration in microbial species across various bodily sites during PDAC tumorigenesis. Notably, Porphyromonas gingivalis, Treponema denticola, Peptoanaerobacter stomatis, Propionibacterium acidifaciens, Porphyromonas endodontalis, Filifactor alocis, etc., sequentially increased along PDAC progression in pancreatic tissue, whereas bacteria commonly used as probiotics Bifidobacterium breve, Lactiplantibacillus plantarum, etc., declined. Furthermore, the sequentially escalating trends of Peptoanaerobacter stomatis and Propionibacterium acidifaciens during PDAC tumorigenesis were mirrored in duodenal fluid and saliva. Porphyromonas gingivalis, Porphyromonas endodontalis, and Filifactor alocis, which intensified from CP to stage Ⅳ PDAC in pancreatic tissue, were also found to be enriched in saliva of patients with short-term survival (STS) compared with those with long-term survival (LTS). Conclusions Salivary and duodenal microorganisms were prominent factors in shaping pancreatic microbial landscape in PDAC context. Further exploration of these microbial entities is imperative to unravel their specific roles in PDAC pathogenesis, potentially yielding insights for future therapeutic strategies.